JURIDICAL ANALYSIS OF THE REGULATION MINISTRY OF LAW AND HUMAN RIGHTS NO 10 OF 2020 CONCERNING THE RELEASE OF CRIMINANTS IN THE COVID 19 PANDEMIC - Siregar, Fitria Ramadhani (International Proceeding of Law and Economic, 2020)
The solution to preventing the spread of Covid-19 is not to gather in crowded and crowded places. This solution can work with people who are free, but not with prisoners and prisoners. Prisoners who are serving sentences in correctional institutions can be said that their space is very limited because prisons in Indonesia can be said to be overcapacity. To overcome this problem, a policy was issued in the form of a regulation, namely the Minister of Law and Human Rights Regulation Number 10 of 2020, but this regulation is considered ineffective if it is implemented in Indonesia because prisoners who are released in the Covid-19 pandemic situation make the situation even more tense, because the inmates confess with new crimes for his survival. This research uses normative legal research methods. Normative legal research is literature-based research, the focus of which is to analyze primary and secondary legal materials. This research uses the method of collecting data by means of library research (Library Research). The policy of releasing prisoners in the midst of a pandemic as it is today is one of giving prisoners rights in the form of humanity. The policy of providing assimilation and integration to inmates in prisons and remand centers is also carried out on the recommendation of the United Nations for the whole world. the implementation of this, and resulted in the inmates committing new crimes for their survival as humans.